Nutritional Status of Older Adults in Antioquia and its Relationship with Diseases and Medication Use (2023)
ABSTRACT: Introduction: Nutritional status (NS) of older adults (OA) can be affected by aging as well as by diseases and medication use. Objective: To determine the NS of OA in Antioquia and its relationship with diseases and medication use. Methods: A cross-sectional study derived from the 2018-2019 Antioquia Food and Nutrition Profile (PANA) was conducted. Information from 1816 OA was collected regarding sociodemographic aspects, NS, diseases, and medication use. Binary logistic regression was applied to establish the association of NS with multimorbidity and polypharmacy. Results: The majority of OA were female, aged 60-69, and of low educational and socioeconomic status. About 38.5% of OA were overweight, and 20.3% were underweight; according to the Mini Nutritional Assessment (MNA), 33.7% were at risk of malnutrition, and 3.5% were already malnourished. Based on calf circumference, 13.5% were at potential risk of malnutrition, and according to waist circumference, 51.8% had abdominal obesity. Multimorbidity was observed in 49.8% of OA, and polypharmacy in 29.6%. After adjusting for socioeconomic variables, statistically significant associations persisted between multimorbidity and risk of malnutrition (OR = 1.76), malnutrition as per MNA (OR = 5.25), and abdominal obesity (OR = 1.57). Concerning polypharmacy, significant associations were found with the risk of malnutrition as per MNA (OR = 2.04) and abdominal obesity (OR = 1.61). Conclusions: In OA, the risk of malnutrition and abdominal obesity increases multimorbidity and polypharmacy, while malnutrition is only associated with a higher number of diseases.